CELSO COSTANTINI DAN MISI DI TIONGKOK: Sebuah Pergulatan Menjalankan Misi Yang Kontekstual - Hermanto, Antonius (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2020)
Celso Costantini had a Catholic Mission in China from 1922 to 1933. At the beginning he felt something wrong with the method of the Mission in China. Catholic Church had existed in China for centuries, but Celso found no local bishop nor clerics who led a Mission region. All Mission regions were led by foreign missionaries. Besides, Celso also saw antipathy against Catholic church. Catholic Church was considered as a foreign religion which wanted to conquer China. This could not be separated from political domination on Catholic Mission. Protectorate system had mixed Catholic Mission with the political interests of European countries. Catholic Mission was controlled by governments, not by the Church itself. A lot of strategic decisions of the Mission were made by the government. The local church just followed the government’s instructions. The Holy See was not involved in the process of making decisions concerning the Mission in China. As a result, Catholic Mission was almost identical to colonial politics of European countries. Celso Costantini carried out the guidance of Maximum Ilud  in his Mission in China. He realized that was in the tension between the Church’s Mission and the political interest of European countries. He understood that he was not a representative of a country, but of the Church as a religious institution. Therefore, Celso distanced himself from political interest whenever possible. He was close to the government, but he refused to be intervened. Celso tried to make Catholic Church mingle with local society so that the Church could be established and bring God’s kingdom among Chinese community. One of Celso’s efforts was the organization of Shanghai Synod in 1924. The Synod produced strategic decisions about the establishment of seminaries, the education of local local seminarians, and cultural promotion as a means of spreading faith. The Synod also had an important role in the ordination of the first six Chinese bishops in 1926 by Pope Pius XI. Celso’s Mission for eleven years in China opened a new hope of the birth of Chinese Catholic Church.